Navigating Legal Complexities: An Empirical Exploration of Minority Shareholders’ Rights in Indonesia’s Corporate Governance Framework - Muhammad Hafid Adhi Nugraha; Albertus Sentot Sudarwanto; Hari Purwadi; Puijono Puijono (CV. Dyoqu Publishing and Management, 2025)
Background: In the context of limited liability companies in Indonesia, minority shareholders often encounter structural disadvantages due to the dominance of majority shareholders. Despite having derivative rights as a legal safeguard, exercising these rights in practice remains a complex challenge. Aims: This research explores the alignment between legal norms and actual practices related to derivative actions initiated by minority shareholders. It focuses on uncovering the systemic barriers they face and proposing pathways for improving legal implementation. Method: The study uses an empirical legal research approach. Data were obtained through interviews with minority shareholders in three companies, supported by doctrinal analysis of statutory provisions and legal theories on protection and effectiveness. Result: The findings indicate three main obstacles: limited financial capacity to initiate lawsuits, political dynamics within shareholder meetings, and insufficient understanding of legal procedures. These issues hinder access to justice and weaken the intended function of minority protection under company law. Conclusion: Although the legal framework in Indonesia recognizes derivative rights, its application remains far from effective. Achieving fairness requires procedural reform, stronger institutional support, and better legal literacy among minority shareholders